Adobe FrameMaker 7.0 - Adobe Systems (San Jose, CA : Adobe Systems, 2002)
Software for publishing long documents across multiple channels. Includes support for standard and enhanced HTML and XML. Also supports creation of structured PDF files.
Keywords: Desktop publishing